Development of STEM-PJBL based Science electronic worksheets to Improve Students' Collaboration Skills - Diana Rossa Martatiyana; Hadi Nasbey; Nidya Chandra Muji Utami (Jurnal Penelitian Pendidikan IPA, 2024)
Learning in the 21st century focuses on the use of advanced technology. At the elementary school level, digital-based learning innovation is important in creating a dynamic and interesting learning environment. This research aims to develop STEM-PjBL based e-LKPD and determine its validity and effectiveness on students' collaboration skills. This development uses a 4D model made by Thiagarajan which consists of 4 stages, namely Define, Design, Development and Disseminate.  With quantitative and qualitative data analysis techniques. Expert validation results show 86.9% is very valid and suitable for use. The responses of students and teachers showed very good results and were quite effective in supporting the improvement of students' collaboration skills, as seen from the n-gain scores of 0.5 and 0.4 in the "medium" category.